2016
DOI: 10.3389/fpsyg.2016.01720
|View full text |Cite
|
Sign up to set email alerts
|

When the Eyes No Longer Lead: Familiarity and Length Effects on Eye-Voice Span

Abstract: During oral reading, the eyes tend to be ahead of the voice (eye-voice span, EVS). It has been hypothesized that the extent to which this happens depends on the automaticity of reading processes, namely on the speed of print-to-sound conversion. We tested whether EVS is affected by another automaticity component – immunity from interference. To that end, we manipulated word familiarity (high-frequency, low-frequency, and pseudowords, PW) and word length as proxies of immunity from interference, and we used lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…However, a different interpretation is also possible. It may be the case that experts do have an internal unfolding-rhythm that generates lagged representations, but they are faster or more efficient in dealing with them: the temporal representations of bar 1 emerged on bar 2, but experts were more efficient than non-experts in processing them in parallel with the initial (gaze-concurrent) processing of bar 2 (see Silva et al, 2016). This would be consistent with the fact that both experts and non-experts showed effects in the same direction (see Figure 4), but only non-experts reached significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a different interpretation is also possible. It may be the case that experts do have an internal unfolding-rhythm that generates lagged representations, but they are faster or more efficient in dealing with them: the temporal representations of bar 1 emerged on bar 2, but experts were more efficient than non-experts in processing them in parallel with the initial (gaze-concurrent) processing of bar 2 (see Silva et al, 2016). This would be consistent with the fact that both experts and non-experts showed effects in the same direction (see Figure 4), but only non-experts reached significance.…”
Section: Discussionmentioning
confidence: 99%
“…Something similar happens when reading text aloud: when a word n is being articulated, the eye is often gazing at n+1 or n+2 (the following words), processing ahead of the motor output. This is named the eye-voice span (Buswell, 1921;De Luca, Pontillo, Primativo, Spinelli, & Zoccolotti, 2013;Inhoff, Solomon, Radach, & Seymour, 2011;Laubrock & Kliegl, 2015;Pan, Yan, Laubrock, Shu, & Kliegl, 2013;Silva, Reis, Casaca, Petersson, & Faísca, 2016). The benefit of these gaze-lagged motor outputs (hand or voice) is to afford fluency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Important, the current study for the first time controlled for the reading strategies elicited by different words by means of eye movement recording. That is, all stimuli (high- and low-frequency words and pseudowords) to be included were selected after being previously tested in an independent reading task with 40 undergraduate students, while eye movements were recorded (SMI hi-speed eye tracking system, 1,250 Hz; see Silva et al., 2016, for a detailed description of the paradigm). In this task, words were arranged in six sets of matrices corresponding to the orthogonal manipulation of familiarity (high- and low-frequency words and pseudowords) and word length (short, long); each matrix comprised 12-to-15 items arranged in a 3 × 4/5 layout and 5 matrices for each set were presented (in total, 80 × 3 experimental stimuli plus fillers).…”
Section: Methodsmentioning
confidence: 99%
“…According to Buswell, a skilled reader will tend to maintain a significant average span between the eye and the voice, while a novice reader will tend to keep the eye and voice very close together, in many cases not moving the eye from a word until the voice has pronounced it [6]. Silva et al [17] demonstrate in their experience that the word familiarity and the word length have a strong effect on the eye-voice span. Laubrock and Kiegl showed that the EVS is constantly regulated [10] thought the reading time according to cognitive, oculomotor, and articulatory demands and that the EVS can be used to predict regression, fixations, and saccades which are related to the reading skill.…”
Section: Introductionmentioning
confidence: 99%